Assessment of filtering properties of asynchronous electric drive with pulse width modulation - Belousov Igor; Samoseiko Veniamin; Saushev Alecsandr (E3S Web of Conferences, 2022)
The process of pulse-width modulation in the converter-motor system is considered. It is noted that the main task of pulse width modulation of voltage formed by the electronic key converter in the converter-motor system is to reduce current pulsations during the modulation period. It is established, that the dynamic process of current change in the electric machine during the period of pulse-width modulation can be approximated by R, L filter. It is shown, that the most important task of pulse-width modulation is minimization of modulation error by current in electric motor. The analysis of possible criteria of estimation of modulation process quality in control systems of electric drive is carried out. It is noted that as a criterion of optimality to assess the quality of modulation in the converter-electromotor system, it is advisable to use the integral quadratic criterion of relative error, called the local variance of the current, as well as the average value of the local variance of the current at the period of the modulating function, called the integral variance of current. The process of estimating the filtering ability of electric machines as part of the electric drive is considered. A system of basic values based on nominal values of electric motor stator voltage, its nominal angular speed and nominal stator current has been selected. The index of filtering properties of the load considering introduction of basic values has been proposed. The equations of an asynchronous electric machine with constant coefficients in the complex form of writing are given. The dependency of the real part of roots of the characteristic equation for an asynchronous machine as a function of angular speed of the rotor rotation is constructed. An analytical expression for the estimation of the filtering properties of asynchronous machines is obtained. The comparison of different types of electric machines according to this parameter is made.